Escuela de Artes y Oficios Oportunidad Para Todos (2022)
We understand that a quality and cultural education is one that forms better human beings, citizens with ethical values, respectful of the public, who exercise human rights, they fulfill their duties and live in peace. An education that generates legitimate opportunities of progress and prosperity for them and for the country.